MATHEMATICAL REPRESENTATION TRANSLATIONS OF JUNIOR HIGH SCHOOL STUDENTS ON QUADRATIC FUNCTION GRAPH MATERIAL - Alyani, Nabila Nur; Subanji, Subanji (Math Educa Journal, 2024)
Mathematical representation translation plays an important role in the learning process, as it connects different forms of representation. This study aims to describe the translation of mathematical representations by students, specifically translating verbal representations into graphs, in solving contextual problems related to quadratic function graphs. The choice of this topic is based on the common difficulties students face in drawing graphs and understanding related problems. The subjects of this study were six ninth-grade students from MTsN 1 Kota Malang, grouped into three categories based on their mathematical proficiency: high, medium, and low. This research uses a qualitative approach, with tests and interviews as data collection instruments. The subjects were selected using purposive sampling. Data analysis was conducted through data triangulation involving data reduction, presentation, and conclusion drawing. The results show that, in the Unpacking the Source stage, students with high and medium proficiency were more accurate in graphing than students with low proficiency. At the Preliminary Coordination stage, high and medium proficiency students were able to perform calculations to determine the function formula, while low proficiency students struggled to identify the appropriate steps. At the Constructing the Target stage, high and medium proficiency students were able to plot the graph correctly according to the obtained coordinates, while low proficiency students had difficulty placing the coordinates. This study indicates that the translation of representations is closely related to students' conceptual understanding and problem-solving abilities.